Draw DH perpendicular to AE.
By the Side-Angle-Side postulate ΔABE = ΔBEF.
this is the enitre answer: https://web2.0calc.com/questions/in-square-abcd-e-is-the-midpoint-of-line-bc-and-f-is-the-midpoint-o...
Answer:
√26 ≈ 5.1 units
Step-by-step explanation:
√(x₂ - x₁)² + (y₂ - y₁)²
√(3/2 - 5/2)² + (8 - 3)²
√(-1)² + (5)²
√1 + 25
√26
Answer:
(f+g)(x) = x^3 - 3x + 2
Step-by-step explanation:
Find (f+g)(x) by adding together f(x) = -3x + 2 and g(x) = x^3:
(f+g)(x) = -3x + 2 + x^3, or, in standard form,
(f+g)(x) = x^3 - 3x + 2
Answer:
1. 72, 2. 36, 3. 80, 4. 54
Step-by-step explanation: